2009
DOI: 10.1007/s10620-009-0920-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Low-Dose Aspirin-Induced Gastric Mucosal Injury and Intragastric pH in Healthy Volunteers

Abstract: Aspirin might induce gastric mucosal injury by affecting the mucosal microvessels in an acid-dependent manner. Sustained maintenance of the intragastric pH at an elevated value is necessary to prevent gastric mucosal damage induced by aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
3
28
0
1
Order By: Relevance
“…Aspirin can induce gastric mucosal injury by affecting the mucosal microvessels in an acid-dependent manner as is suggested by a recent study comparing aspirin versus aspirin plus different doses of rabeprazole. Thus, it is suggested that sustained elevation of the intragastric pH is necessary to prevent gastric mucosal damage induced by aspirin [8]. …”
Section: Aspirinmentioning
confidence: 99%
“…Aspirin can induce gastric mucosal injury by affecting the mucosal microvessels in an acid-dependent manner as is suggested by a recent study comparing aspirin versus aspirin plus different doses of rabeprazole. Thus, it is suggested that sustained elevation of the intragastric pH is necessary to prevent gastric mucosal damage induced by aspirin [8]. …”
Section: Aspirinmentioning
confidence: 99%
“…Moreover, since the benefits of dual anti-platelet therapy (DAT) with LDA and clopidogrel have been confirmed in the treatment or prevention of cardiovascular and cerebrovascular disease, DAT, but not monotherapy with LDA or clopidogrel, is often used in complicated patients such as after drug-eluting stent implantation, where DAT therapy is required for more than 6 months in order to avoid potentially catastrophic stent thrombosis. The efficacy of DAT for patients with a past history of cardiovascular events is well supported in the medical literature.The downside of DAT is foregut mucosal injury, which affects almost all recipients, regardless of symptoms [1][2][3]. Thus, much attention has been focused on the prevention of mucosal injury, which can manifest as severe gastrointestinal hemorrhage or perforation.…”
mentioning
confidence: 99%
“…The recommended doses of aspirin for the prevention of cardiovascular and cerebrovascular disease are 75-300 mg/day, though when benefits and adverse risks are taken into account, the optimal dose of aspirin is no more than 100 mg/day [6]. A gastric mucosal damage score of [1 according to the modified Lanza criteria [7] is observed in 93 % of healthy volunteers after administration of LDA, irrespective of age and duration of therapy [2]. Nevertheless, although the detailed biological mechanism of clopidogrel-induced mucosal damage is unclear, clopidogrel is less likely than LDA to damage the foregut mucosa, which belies the observation that clopidogrel often causes massive gastrointestinal bleeding due to its potent anti-platelet effects by the inhibition of the purinergic P2Y12 receptor expressed on the platelet cell membrane [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations